Desistance from Crime during the Transition to Adulthood: The Influence of Parents, Peers, and Shifts in Identity. (May 2020) - Copp, Jennifer E.; Giordano, Peggy C.; Longmore, Monica A.; Manning, Wendy D.
Objectives: Research on criminal continuity and change has traditionally focused on elements of the adult life course (e.g., marriage and employment); however, recent social and economic changes suggest the need to consider a broader range of factors. In addition, researchers have increasingly recognized the importance of identity changes in the desistance process. Methods: Using five waves of structured data from the Toledo Adolescent Relationships Study (TARS), we examined identity changes, shifts in involvement with delinquent peers, and variability in closeness with parents as influences on desistance. In-depth interviews with a subset of TARS respondents offered a person-centered lens on individual and social processes associated with variability in criminal behavior. Results: Findings indicated that identity changes were associated with declines in offending. In addition, changes in parental closeness and the extent of affiliation with antisocial peers contributed to patterns of offending, net of these subjectively experienced cognitive changes. Conclusions: Cognitive processes are important to desistance. However, they do not independently provide a path to sustained behavioral change. Social experiences, including changes in relationships/supports from parents and affiliation with delinquent peers, also figure into change processes. We discuss the implications of our findings for future research and programmatic efforts.